2022
DOI: 10.3390/su14148669
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomenon of Technostress during the COVID-19 Pandemic Due to Work from Home in Indonesia

Abstract: The regulation of work from home (WFH) was suddenly instructed by many companies in Indonesia at the beginning of the COVID-19 pandemic. It improved the demand for information and communication technology, which triggered the emergence of technostress among workers. Therefore, this study aimed to analyze the technostress phenomenon in Indonesia due to the regulation of WFH by involving 819 respondents collected using an online questionnaire. This quantitative study using an SEM-Model investigated the correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 79 publications
0
4
0
2
Order By: Relevance
“…The variables in this study can be stated to have consistent reliability because they have a Cronbach alpha above 0.7, as presented in Table 4. Farmania et al (2022) found that technostress positively affected productivity and also found the possibility that productivity was not triggered by their desires but by pressure due to the pandemic. In addition, other studies also support this research, i.e.…”
Section: Measurement Model Evaluationmentioning
confidence: 99%
“…The variables in this study can be stated to have consistent reliability because they have a Cronbach alpha above 0.7, as presented in Table 4. Farmania et al (2022) found that technostress positively affected productivity and also found the possibility that productivity was not triggered by their desires but by pressure due to the pandemic. In addition, other studies also support this research, i.e.…”
Section: Measurement Model Evaluationmentioning
confidence: 99%
“…Thus, being hyperconnected also increases technostress-stress caused by workrelated technology usage, which can lead to fatigue, restlessness, and physical discomfort (Singh et al, 2022). Owing to the increased use of new and familiar digital technologies (Farmania et al, 2022), technostress can increase psychological strain, causing technology exhaustion and decreased well-being (Singh et al, 2022). Given that remote employees rely on higher usage of digital technologies, unmitigated technostress serves to increase their risks of burnout and distress.…”
Section: Hyperconnectivitymentioning
confidence: 99%
“…Many firms have started implementing a new working method to effectively adapt to these transitions, i.e., teleworking or a policy allowing employees to work from home. This change has significantly impacted how businesses operate and the interaction between employees and employers, adversely resulting in job stress (Irawanto et al, 2021) and technostress (Farmania & Elsyah, 2022) due to technological devices and limited social encounters. COVID-19 also brings implications for management control change that theoretically influences employee behavior in desirable ways (Merchant & Van der Stede, 2017).…”
Section: The Situation In the Covid-19 Pandemicmentioning
confidence: 99%